Firm-level evidence of shifts in the supply of credit - Karolina Holmberg (Sveriges Riksbank, 2013)
Using panel data of 68,800 small and large firms, I examine whether firms are subject to shifts in the supply of credit over the business cycle. Shifts in the supply of credit are identified by exploring how firms substitute between commitment credit - lines of credit - and non-commitment credit. I find that firms on average rely more on commitment credits when monetary policy is tight and when the financial health of banks is weaker. The results are consistent with a bank lending channel of monetary policy and with shifts in the supply of credit following deteriorations in banks' balance sheets.
Keywords: E32; E44; E51; G01; G21; 330; Bank Lending Channel; Bank Capital; Business Fluctuations